Aloe Vera Cultivation and Post-Harvest Processing for Daily Life - Sutopo, Yeri; Rudyatmi, Ely; Rohman, Shohihatur; Setiyanto, Denny Firman; Dewa, Pramaditya Putra Komala; Andhika, Pedro (Journal of Community Empowerment, 2024)
Aloe vera was often wasted, even though it actually has many benefits. During a morning walk in the Taman Kradenan Asri housing complex, many aloe vera plants were found to be thrown away. When asked to the owner of the plant, why were so many of his aloe vera plants thrown away? The owner of the aloe vera replied that this plant grows very quickly, even though its use was only a little, namely for washing hair as a shampoo supplement and its mucus to help heal minor wounds. This fact encouraged community service activities to be carried out in the housing complex, namely through training for mothers of the Dasa Wisma. This community service activity aims to describe skills and knowledge in developing higher quality aloe vera which could later be used to produce processed products for mothers who are members of the Dasa Wisma in RW 11, Sukorejo Village in Semarang City. The results of this community service show that: (1) The knowledge of the local women who participated in the training and mentoring regarding Aloe Vera cultivation and post-harvest processing for daily life in RW 11, Sukorejo Village, Gunungpati District, Semarang City, most of the 50% of participants had knowledge in the category Enough.; (2) Skills of local women who participated in training and mentoring on Aloe Vera Cultivation and Post-Harvest Processing for Daily Life in RW 11, Sukorejo Village, Gunungpati District, Semarang City, the majority of whom, namely 55.5% of participants, had skills in the sufficient category.